THE IMPORTANCE OF USING GIS IN INCREASING THE EFFICIENCY OF AGRICULTURAL FARMS - A BIBLIOMETRIC APPROACH - Mirela PLESA; Liviu MARCUTA; Alina MARCUTA; Alexandru FINTINERU; Andreea Roxana FIRĂŢOIU; Ovidiu GUSAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Modern agriculture faces many challenges, including the need to feed a growing global population, cope with climate change, soil degradation and biodiversity loss. GIS technology provides solutions to these problems through its ability to collect, analyze and visualize complex geospatial data. This technology allows farmers and researchers to make informed decisions based on accurate and up-to-date data, which is why they play an essential role in modern agriculture, enabling the development of innovative solutions to global challenges, contributing to more efficient, sustainable and productive agriculture higher. In this work, we proposed that, starting from the existing data in the WOS and Scopus international databases, to analyze the existing research with the aim of identifying the major trends in GIS-related research, which includes both the evaluation of the volume and the temporal distribution of publications and the identification of popular and emerging research topics, by analyzing citations and impact factors, we can evaluate the influence and relevance of research in the field of GIS. Additionally, through a comprehensive review of existing literature and the application of bibliometric analysis, this research has identified gaps and highlighted future research needs within the GIS domain, this being essential for the direction of future research directions and for the development of new projects and initiatives that to address these gaps as well. Following the restrictions applied, it started from a number of 81,566 articles, the refinement establishing a number of 903 articles that address issues related to the use of GIS in agricultural farms, of which only 19 are those that analyze their role in assessing the efficiency of our activities, the results demonstrate that GIS is a dynamic and expanding research field with broad applicability and significant impact. Our analysis of collaboration networks indicates that the United States, China, the United Kingdom, and Australia lead in international publications and collaborations, essential for the innovative application of GIS. Our research shows a significant increase in GIS-related publications, reflecting growing academic interest and the integration of fields such as environmental monitoring, natural resource management, and precision agriculture.